2015
DOI: 10.3390/ijms160612092
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Propofol Overdose Causes Vascular Hyperpermeability by Reducing Endothelial Glycocalyx and ATP Production

Abstract: Prolonged treatment with a large dose of propofol may cause diffuse cellular cytotoxicity; however, the detailed underlying mechanism remains unclear, particularly in vascular endothelial cells. Previous studies showed that a propofol overdose induces endothelial injury and vascular barrier dysfunction. Regarding the important role of endothelial glycocalyx on the maintenance of vascular barrier integrity, we therefore hypothesized that a propofol overdose-induced endothelial barrier dysfunction is caused by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Lin et al reported that propofol significant decreases in the NAD+/ NADH ratio, in ATP concentrations, is also similar to our results, because the reduction of NAD+/NADH ratio indicates that failure of the electron transport system at mitochondria [40][41][42][43]. Tsuchiya et al reported that propofol induce mitochondrial pathway-dependent apoptosis in human promyelocytic leukemia (HL-60) cell lines [44] that is also similar to our results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Lin et al reported that propofol significant decreases in the NAD+/ NADH ratio, in ATP concentrations, is also similar to our results, because the reduction of NAD+/NADH ratio indicates that failure of the electron transport system at mitochondria [40][41][42][43]. Tsuchiya et al reported that propofol induce mitochondrial pathway-dependent apoptosis in human promyelocytic leukemia (HL-60) cell lines [44] that is also similar to our results.…”
Section: Discussionsupporting
confidence: 81%
“…PRIS mostly occurs in younger children, and some of the main symptoms include acidosis, rhabdomyolysis, myoglobinuria, and subsequently multiple organ failure [37,38]. There are many reports of PRIS, mostly involving mitochondrial failure, with some reports noting intralipid involvement [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…As a synthetic component of ATP, creatine phosphate sodium can increase the level of ATP in vivo , and thereby promote the metabolism of these drugs in the liver. 23 25 Experiments have shown that creatine phosphate sodium also buffers energy supplies and improves mitochondrial efficiency in the brain. 26 , 27 As an antioxidant, creatine phosphate sodium can protect brain and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that propofol, as a lipophilic agent, may disturb the continuity of cell membranes mechanically and reduce the glycocalyx barrier on endothelial cells. 40 Thus the direct effect of propofol on endothelial cells, depending strictly on its physicochemical properties, may further disturb the release of the endothelial mechanism of t-PA, PAI-1 and other factors. Moreover, there are some studies indicating a direct effect of propofol on shape and viscoelasticity of erythrocytes and platelets related to intercalation of propofol in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%